2009
DOI: 10.1111/j.1365-2966.2009.14618.x
|View full text |Cite
|
Sign up to set email alerts
|

A downturn in intergalactic C iv as redshift 6 is approached

Abstract: We present the results of the largest survey to date for intergalactic metals at redshifts z > 5, using near‐IR spectra of nine quasi‐stellar objects with emission redshifts zem > 5.7. We detect three strong C iv doublets at zabs= 5.7–5.8, two low‐ionization systems at zabs > 5 and numerous Mg ii absorbers at zabs= 2.5–2.8. We find, for the first time, a change in the comoving mass density of C iv ions as we look back to redshifts z > 5. At a mean 〈z〉= 5.76, we deduce ΩC iv= (4.4 ± 2.6) × 10−9 which implies a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
187
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(211 citation statements)
references
References 71 publications
23
187
1
Order By: Relevance
“…Inspection of the Voigt profile Doppler parameters in Table 2 shows a high average b, similar to what was described in Ryan-Weber et al (2009). This width is more likely to represent the full velocity spread of a suite of narrow components, rather than a large, single component.…”
Section: IV Sample and Measurementsmentioning
confidence: 70%
See 2 more Smart Citations
“…Inspection of the Voigt profile Doppler parameters in Table 2 shows a high average b, similar to what was described in Ryan-Weber et al (2009). This width is more likely to represent the full velocity spread of a suite of narrow components, rather than a large, single component.…”
Section: IV Sample and Measurementsmentioning
confidence: 70%
“…Broadly speaking, we recover most lines (>80%) above N C iv = 10 14 and relatively few (<10%) below N C iv = 10 13.2 , with the 50% level occurring near 10 13.7 . Thus our survey sits between the parameter space explored by Becker et al (2009), who are complete to lower N C iv over a significantly smaller path length, and Ryan-Weber et al (2009) who have a comparable path length but slightly lower completeness.…”
Section: Completeness Estimatesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also relatively straightforward to model because it arises in gas that is optically thin to ionizing photons and lies far enough away from galaxies that the local radiation field may be neglected to first order. Its overall mass density is robustly observed to decline slowly with increasing redshift (Songaila 2001;Becker et al 2009;Ryan-Weber et al 2009;D'Odorico et al 2010D'Odorico et al , 2013Simcoe et al 2011;Becker et al 2011;Cooksey et al 2013). Numerous studies have shown that the observed decline can readily be accommodated by numerical simulations (Oppenheimer & Davé 2006;Oppenheimer et al 2009;Cen & Chisari 2011).…”
Section: Introductionmentioning
confidence: 87%
“…Intergalactic C IV and C II absorbers are observed along sightlines to quasars out to the highest redshifts probed (Songaila 2001;Ryan-Weber et al 2006;Becker et al 2009;Ryan-Weber et al 2009;Simcoe et al 2011;D'Odorico et al 2013;Becker et al 2011). They occur naturally in cosmological hydrodynamic simulations in which galactic outflows expel metals out to the virial radius and beyond (Theuns et al 2002;Cen et al 2005; Oppenheimer & Davé 2006, 2008Oppenheimer et al 2009;Cen & Chisari 2011), opening up the possibility of using models to interpret them as tracers of star formation, outflows, and the ultraviolet ionizing background (UVB).…”
Section: Introductionmentioning
confidence: 99%